DOI: 10.14264/uql.2019.85
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and opportunities to improve livestock production and health, and reduce zoonotic risks in small-scale native chicken, cattle and small ruminant farms in the Central Dry Zone of Myanmar

Abstract: The Central Dry Zone (CDZ) supports 10 million people whose livelihoods depend on dry-land agriculture and small-scale livestock rearing. The CDZ has the highest livestock concentration in Myanmar, but characteristics of livestock production and health in this region have not been evaluated in detail. There is a need to understand the opportunities and limitations and for livestock production in the CDZ in order to develop methods to improve livestock production and disease control, to enhance the financial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 177 publications
(299 reference statements)
2
0
0
Order By: Relevance
“…This indicates that educating people is of paramount importance in increasing the proportion of livestock owners with appropriate anthrax disease prevention practices. Other earlier studies also reported similar findings [17,20,21].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates that educating people is of paramount importance in increasing the proportion of livestock owners with appropriate anthrax disease prevention practices. Other earlier studies also reported similar findings [17,20,21].…”
Section: Discussionsupporting
confidence: 83%
“…This might because urban dwellers have better access to information and veterinary services which enable them to prevent anthrax appropriately. In addition, urban dwellers are more likely to get animal health care services since most vaccinations and information campaigns focus on areas with better infrastructure, such as roads [17]. This observation is supported by previous reports which reveal that the risk for zoonosis is significantly higher among rural farms compared to peri or urban ones (P < 0.05), and rural communities commonly consume raw milk, meat and blood [15,18,19] .…”
Section: Discussionsupporting
confidence: 53%